We Got Game: 35 Female Athletes Who Changed The World - Weintraub, Aileen; Sarah Green (New York: RP kids, 2021)
Meet thirty-five female athletes who played hard, broke records, and inspired girls around the world. You'll read about the first woman horse jockey to compete in the Kentucky Derby, the number one tennis player in the world, a surfer who lost her arm in a shark attack, and a snow boarder who landed a death-defying jump, along with many others
In English.
H.B
Keywords: Sportives Biographies Ouvrages pour la jeunesse; Autobiography / Social Activists; Women Biography & Women athletes